Intra-cheek immunization as a novel vaccination route for therapeutic vaccines of head and neck squamous cell carcinomas using plasmo virus-like particles. (2nd July 2016) - Macedo, Rodney; Rochefort, Juliette; Guillot-Delost, Maude; Tanaka, Kae; Le Moignic, Aline; Noizat, Clara; Baillou, Claude; Mateo, Véronique; Carpentier, Antoine F.; Tartour, Eric; Bertolus, Chloé; Bellier, Bertrand; et al.
ABSTRACT: Despite current therapy, head and neck squamous cell carcinomas (HNSCCs) arising from various mucosal sites of the upper aero-digestive tract frequently relapse in a loco-regional manner and have a poor prognosis. Our objective was to validate an innovative mucosal route of vaccination using plasmo virus-like particles (pVLPs) in a pre-clinical orthotopic model of HNSCCs. For this purpose, we used pVLP-E7, that are plasmid DNA encoding retroviral virus-like particles carrying a truncated E7 oncoprotein from HPV-16 as antigen model, to vaccinate mice bearing pre-established TC-1 tumors implanted into the buccal mucosa. pVLP-E7 were combined with clinical grade TLR agonists (Imiquimod and CpG-ODN). In this pre-clinical orthotopic model, whose tumor microenvironment resembles to those of human HNSCCs, different mucosal vaccination routes were tested for their ability to elicit efficient immune and antitumoral responses. Results showed that mucosal intra-cheek (IC) vaccinations using pVLP-E7, comparatively to intradermic vaccinations (ID), gave rise to higher mobilization of mucosal (CD49a + ) CD8 + specific effector T cells in both tumor draining lymph nodes (TdLNs) and tumor microenvironment resulting in better antitumor effects and in a long-term protection against tumor rechallenge. In vivo CD8 + depletion demonstrated that antitumoral effects were fully dependent upon the presence of CD8 + T cells. Validation of IC mucosal vaccinations with pVLPs combined with adjuvants using a pre-clinical orthotopic model of HNSCC provides valuable pre-clinical data to rapidly envision the use of such therapeutic vaccines in patients with HNSCCs, inasmuch as vaccinal components and adjuvants can be easily obtained as clinical grade reagents.